2007
DOI: 10.1145/1190215.1190266
|View full text |Cite
|
Sign up to set email alerts
|

Interprocedural analysis of asynchronous programs

Abstract: An asynchronous program is one that contains procedure calls which are not immediately executed from the callsite, but stored and "dispatched" in a non-deterministic order by an external scheduler at a later point. We formalize the problem of interprocedural dataflow analysis for asynchronous programs as AIFDS problems, a generalization of the IFDS problems for interprocedural dataflow analysis. We give an algorithm for computing the precise meet-over-valid-paths solution for any AIFDS instance, as well as a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 23 publications
(31 reference statements)
0
79
0
Order By: Relevance
“…Decidability is ensured by allowing only a bounded number of updates to the shared variables. Dataflow analysis for asynchronous programs wherein threads can fork off other threads but where threads are not allowed to communicate with each other has also been explored [13,5] and was shown to be EXPSPACEhard, but tractable in practice.…”
Section: Resultsmentioning
confidence: 99%
“…Decidability is ensured by allowing only a bounded number of updates to the shared variables. Dataflow analysis for asynchronous programs wherein threads can fork off other threads but where threads are not allowed to communicate with each other has also been explored [13,5] and was shown to be EXPSPACEhard, but tractable in practice.…”
Section: Resultsmentioning
confidence: 99%
“…7 Though this exploration corresponds to an underapproximation of the program semantics, the complexity is lower than the precise EXPSPACE-complete explorations of Sen and Viswanathan [37] and Jhala and Majumdar [19] for non-preemptive asynchronous programs. Additionally, our underapproximation has a lower complexity than the PSPACE-hard underapproximation [5] used by Jhala and Majumdar [19]'s algorithm, which corresponds to our (non-preemptive) bounded bag semantics (see Scheduler 2). Note in the case of preemptive programs, the analysis problem is generally undecidable [36].…”
Section: Complexity Of Depth-first Schedulingmentioning
confidence: 99%
“…Sen and Viswanathan [37] introduced the model explicitly to reason about event-driven programs, and showed that control-state reachability is EXPSPACE-hard; Ganty and Majumdar [14] tightened this result to show that the problem is EXPSPACE-complete. To combat this high worst-case theoretical complexity, Jhala and Majumdar [19] suggest a scheme that combines an underapproximate and an overapproximate computation of the reachable states.…”
Section: Related Workmentioning
confidence: 99%
“…A recent paper [11] delineates the decidability boundary for the model checking problem for systems with finitely many Interacting Pushdown Systems synchronizing via the standard primitives -locks, rendezvous and broadcasts. The dataflow analysis for asynchronous programs wherein threads can fork off other threads but where threads are not allowed to communicate with each other has been explored [9].…”
Section: Conclusion and Related Workmentioning
confidence: 99%